Effect of 2-D nanomaterials on sensitivity of plasmonic biosensor for efficient urine glucose detection - Yadav, Archana; Kumar, Shatrughna; Kumar, Anil; Sharan, Preeta (Frontiers in Materials, 2023)
This paper presents a multi-layered Kretschmann configuration-based Surface Plasmon Resonance (SPR) biosensor for the detection of urine glucose. The modelling, simulation, and analysis has been done by using Silver (Ag) and Gold (Au) layer on low refractive index prism BK-7 separately that created two structures viz structure-I (BK7/Ag/Bio-sample) and Structure-II (BK7/Au/Bio-sample). Urine samples for a non-diabetic person (0–15 mg/dL) and diabetic person (0.625 gm/dL, 1.25 gm/dL, 2.5 gm/dL, 5 gm/dL, and 10 gm/dL) with the corresponding refractive indices of 1.335,1.336,1.337,1.338,1.341,1.347 respectively has been used as a bio-sample that has been put on the top layer of the sensor. To enhance the performance parameters of the proposed plasmonic biosensor, an investigation has been done by using different 2-D nano-materials (Graphene, BP) and TMDC materials (MoS2, MoSe2, WS2, WSe2) layer over the Silicon (Si) layer in both structures in visible wavelength (λ=633 nm) by employing Transfer Matrix Method (TMM). With layer thickness optimization, Structure-I (BK7/Ag (56 nm/ Si (03nm)/ WS2 (0.8 nm)/ Bio-sample) shows a sensitivity of 200 o/RIU which is enhanced up to 1.7 times of the conventional biosensor and 1.3 times of the BK7/Ag (56 nm)/ Si (03 nm)/ Bio-sample biosensor. Whereas in Structure-II (Bk7/Au (50 nm)/Si (03 nm)/BP (0.53 nm)/Bio-sample) with optimized layer thickness, we obtained a sensitivity of 273.4o/RIU which is enhanced up 2.2 times of the conventional biosensor and 1.3 times of the BK7/Au (50 nm)/Si (03 nm)/Bio-sample biosensor. Other performance parameters such as Detection accuracy for Structure-I and Structure-II are 0.5617 degree-1 and 0.134 degree-1 respectively however Figure of merit for Structure-I and Structure-II is 112.35 /RIU and 36.89 /RIU respectively. Therefore, we expect the Structure-I (BK7/Ag (56 nm/ Si (03nm)/ WS2 (0.8 nm)/ Bio-sample) and Structure-II (Bk7/Au (50 nm)/Si (03 nm)/BP (0.53 nm)/Bio-sample) have the potential to detect the glucose concentration with quick response with high sensitivity in terms of the resonance angle shift in SPR curves and also it can be fabricated in the scale of nonorange.